African American Literacies Unleashed : Vernacular English and the Composition Classroom - Ball, Arnetha F., 1950- (Book collections on Project MUSE., 2005)
This pioneering study of African American students in the composition classroom lays the groundwork for reversing the cycle of underachievement that plagues linguistically diverse students. African American Literacies Unleashed: Vernacular English and the Composition Classroom approaches the issue of African American Vernacular English (AAVE) in terms of teacher knowledge and prevailing attitudes, and it attempts to change current pedagogical approaches with a highly readable combination of traditional academic discourse and personal narratives. Realizing that composition is a particular for.